STRATEGI BERALIH KE BAHASA IBU MENURUT TEORI OXFORD (1990) PADA MAHASISWA ANGKATAN 2020 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Syarifa Aini; Nana Rahayu; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The strategy of switching to the mother tongue is used for speaking and involves using the mother tongue for expression without translating it. This research aims to find strategies for switching to the mother tongue used by students of class of 2020 in Japanese conversation. The participants in this study were middle-level students, namely students of class of 2020 of the Japanese language education study program, FKIP Riau University, in Japanese conversation. The purpose of this research is to find out and describe the strategy of switching to the mother tongue used by students of class of 2020 of the Japanese language education study program FKIP Riau University in Japanese conversations. The method used in this research is descriptive method. The research instruments used were interviews and observations. The results of this study indicate that almost all students use the strategy of switching to their mother tongue when speaking Japanese.Keywords: Compensation Strategy, Strategy for Switching to Mother Tongue, Speaking, Japanese